2002
DOI: 10.1038/sj.bjc.6600193
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones, cholecystectomy, and the risk for developing pancreatic cancer

Abstract: We examined the relation between gallstones, cholecystectomy, and the development of pancreatic cancer in the Nurses' Health Study and the Health Professionals Follow-up Study. Among 104 856 women and 48 928 men without cancer at baseline, we documented 349 cases of pancreatic cancer during up to 16 years of follow-up. Participants were classified according to a history of gallstones or cholecystectomy. The age-adjusted relative risk of pancreatic cancer following cholecystectomy or diagnosis of gallstones was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 21 publications
2
21
0
1
Order By: Relevance
“…In this study, we found no significant relationship between gallstones or prior cholecystectomy and pancreatic cancer after controlling for potential confounding variables as shown in Table 3. Our finding is consistent with previous studies (61,62). It is possible that the observed positive association between cholecystectomy and pancreatic cancer in previous studies is confounded by other risk factors such as cigarette smoking, diabetes, chronic pancreatitis, heavy alcohol consumption, or family history of pancreatic cancer.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we found no significant relationship between gallstones or prior cholecystectomy and pancreatic cancer after controlling for potential confounding variables as shown in Table 3. Our finding is consistent with previous studies (61,62). It is possible that the observed positive association between cholecystectomy and pancreatic cancer in previous studies is confounded by other risk factors such as cigarette smoking, diabetes, chronic pancreatitis, heavy alcohol consumption, or family history of pancreatic cancer.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, our findings are consistent with those of the Nurses' Health Study and the Health Professional Follow-up Studies (Schernhammer et al, 2002), and indicate that cholelithiasis is not materially associated with pancreatic cancer risk after major identified confounding factors have been considered. A modestly increased risk was observed 10 years after a diagnosis of cholelithiasis, but no greater excess risk can be found 10 or more years after.…”
Section: Sirsupporting
confidence: 80%
“…The issue of a possible association between gallstones or cholecystectomy and cancer of the pancreas is, however, still open to discussion, because several investigations reported an excess pancreatic risk in patients with gallstones. Apart from the papers quoted in Schernhammer et al (2002), some excess risks were found in cohort studies from the United States (Bansal and Sonnenberg, 1996), Denmark (Johansen et al, 1996), and Sweden (Ye et al, 2001), and case -control studies from the United Kingdom (Cuzick and Babiker, 1989), Greece (Kalapothaki et al, 1993), and Israel (Schattner et al, 1997). The strength of the association, however, was variable across studies, and different potential confounding factors were not always taken into account.…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these three as well as the previous cohort studies have not removed uncertainty about any causal association between cholecystectomy and colon cancer. Other cancers, too, have been studied after cholecystectomy, but the evidence on causality associations with cancers of the pancreas, liver, and stomach is also inconsistent (Ekbom et al, 1996;Johansen et al, 1996;Chow et al, 1999;Schernhammer et al, 2002).…”
Section: Discussionmentioning
confidence: 99%